Effects of a titanate coupling agent on the mechanical and thermo‐physical properties of talc‐reinforced polyethylene compounds. Issue 13 (31st January 2014) - Mehrjerdi, Adib Kalantar; Mengistu, Bemnet Abebe; Åkesson, Dan; Skrifvars, Mikael
ABSTRACT An experimental study was carried out to investigate the effects of a titanate coupling agent on the mechanical properties, moisture absorption, and thermal conductivity of talc‐filled high‐density polyethylene (HDPE). Talc (0–35 wt %) was used as reinforcement particulate filler in an HDPE matrix and samples were prepared in a micro‐compounder and an injection molding machine. Isopropyl tri(dioctyl)phosphate titanate (0.5 wt %) was used as coupling agent. Composites with and without coupling agent were evaluated for changes in mechanical and thermo‐physical properties, morphology, and void content. Addition of the titanate coupling agent most often resulted in an increase in stiffness and tensile strength. Furthermore, both the void content and the elongation at break of composites were reduced. Results also showed that the coupling agent had no effects on the thermal conductivity, thermal diffusivity, and specific heat capacity of the composites. In addition, it was observed that the coupling agent was more effective at low concentrations of filler. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40449.